Compliance with the principles of the perioperative safety process in the context of the work of perioperative nurses - Petra Pavlová; Jana Holá; Jana Holá (University of Ostrava, 2019)
Aim: The main aim was to describe the current state of perioperative safety processes with reference to perioperative nurses' work. Design: To achieve the stated goal, a custom-built "ad hocˮ research design was created, using a combination of qualitative and quantitative methods. The findings of the exploratory qualitative survey were verified by the quantitative survey focused on in this article. Methods: The exploratory survey and Surgical Safety Checklist were the basis for a questionnaire which was designed to be used as a tool for investigation among a set of perioperative nurses in Czech hospitals. The target group of respondents was operating room managers, one representative per healthcare institution. The obtained data were analysed by exploratory statistical methods. Results: More than 96% of the healthcare institutions included in the research sample have formally established procedures: patient identification, verification of the type and side of the operation, checks for patient's history of allergies, and checks of the number of medical devices (n = 68). The survey showed that the respondents perceive safety checks to be of utmost importance in the perioperative procedure (modal value of seven on a scale from one to seven). Conclusion: Using the Surgical Safety Checklist should lead to safety improvements in nursing perioperative care. In most cases, the nursing safety practices formally introduced at respondents' workplaces correspond to WHO recommendations in the form of this Checklist.